Supplemental metaphyseal fixation of severe comminuted distal radius fracture with a mini plate - Kim, Dong Hee; Jin, Jin Woo; Shin, Sung Jin; Lee, Chul Ho; Lee, Sang Hyun (BMC musculoskeletal disorders, 2025)
Backgrounds The treatment of complex distal radius fractures, particularly those involving both intra-articular disruption and significant metaphyseal comminution, remains a considerable surgical challenge. While volar locking plates have become a widely accepted standard for stabilizing these fractures, alone they may not address all fracture patterns. This study presents a surgical approach that incorporates the use of a mini-plate to provide targeted support for the metaphyseal region. We hypothesize that combining a mini-plate for metaphyseal stabilization with a volar locking plate for overall fracture fixation will enhance the structural stability and radiologic outcomes of metaphyseal comminuted distal radius fractures. Subjects and methods Eight cases of distal radius fractures involving comminution extending to the metaphysis treated surgically at Samsung Changwon Hospital during 2013–2023 were retrospectively analyzed. All patients had distal radius fractures with severe comminution at the metaphysis, where an added mini-plate was used to fix the fragments before applying the final volar locking plate. Using patient medical records, the mechanism of injury; presence of osteoporosis; type of fracture; radiologic parameters, final range of motion of the wrist; Mayo score and Disabilities of the Arm, Shoulder, and Hand (DASH) scores were investigated. Results The average age of the participants was 66 years. After a mean follow-up of 30.1 months, all patients achieved proper bone union. The median total range of motion of the wrist joint was 110.6° (40°–170°) at final follow-up. The radiographic parameters showed significant improvement postoperatively compared to preoperatively. The ulnar variance improved from a median of 5 mm to 0.5 mm ( P = 0.013), the median teardrop angle increased from 33° to 59° ( P = 0.012), and the median lateral palmar tilt improved from − 15.5° to 10.5° ( P = 0.033). The median DASH score was 35.6 points, and the median Mayo score was 75.2 points. Conclusion By initially securing larger metaphyseal fragments with mini-plates, we transform a comminuted metaphyseal fracture into a simpler fracture pattern. This approach stabilizes the metaphyseal region, maintains radial length, and facilitates subsequent reduction of intra-articular fractures, thereby simplifying the surgical procedure. This method is a valuable addition to the surgical treatment options for managing such challenging fractures.